A Dictionary And Grammatical Outline Of Chakali - Brindle, Jonathan (My University, 2017)
This book is the first comprehensive monograph dedicated to Chakali, a Southwestern Grusi language spoken by less than 3500 people in northwest Ghana. The dictionary offers a consistent description of word meaning and provides the basis for future research in the linguistic area. It is also designed to provide an inventory of correspondence with English usage in a reversal index. The concepts used in the dictionary are explained in a grammar outline, which is of interest to specialists in Gur and Grusi linguistics, as well as any language researchers working in this part of the world.
Keywords: Chakali; dictionary; Grusi language